2021
DOI: 10.1080/11101849.2021.1910181
|View full text |Cite
|
Sign up to set email alerts
|

Does the mode of anesthesia affect the feto-maternal outcome in category-1 caesarean section? A prospective non-randomized study comparing spinal versus general anesthesia

Abstract: 2021) Does the mode of anesthesia affect the feto-maternal outcome in category-1 caesarean section? A prospective non-randomized study comparing spinal versus general anesthesia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Moreover, the proportions of newborns delivered under general anesthesia who required mask ventilation, intubation and NICU admissions were signi cantly larger than those delivered under spinal anesthesia category one cesarean sections. This nding is consistent with studies performed in Korea, Egypt, Australia and the University of Messina, Italy (8, 9,11,43). Another study performed in Australia also supports this nding in which they showed that there were larger proportions of newborns who required bag mask ventilation, NICU admission, and intubation (27.4%, 29.6%, and 4.9% and 13.5%, 14.6%, and 4.5%, respectively) after delivery under general anesthesia than after spinal anesthesia (9).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the proportions of newborns delivered under general anesthesia who required mask ventilation, intubation and NICU admissions were signi cantly larger than those delivered under spinal anesthesia category one cesarean sections. This nding is consistent with studies performed in Korea, Egypt, Australia and the University of Messina, Italy (8, 9,11,43). Another study performed in Australia also supports this nding in which they showed that there were larger proportions of newborns who required bag mask ventilation, NICU admission, and intubation (27.4%, 29.6%, and 4.9% and 13.5%, 14.6%, and 4.5%, respectively) after delivery under general anesthesia than after spinal anesthesia (9).…”
Section: Discussionsupporting
confidence: 92%
“…Intraoperative and postoperative maternal vital signs were signi cantly higher in the GA group than in the SA group. This is supported by the study performed in Korea and Benha University (11,43).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation